2015
DOI: 10.2135/cropsci2014.10.0690
|View full text |Cite
|
Sign up to set email alerts
|

Phenomorphological Characterization of Vegetable Soybean Germplasm Lines for Commercial Production

Abstract: Growing demand for vegetable soybean [Glycine max (L.) Merr.] has renewed interest in producing the crop in the United States, a significant importer of vegetable soybean despite being the world's largest producer and exporter of grain‐type soybean. Field studies were conducted over 3 yr to(i) compare phenomorphological traits of vegetable and grain‐type soybean and (ii) identify candidate lines for vegetable soybean production in the North Central United States, the nation's leading soybean‐producing region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 15 publications
0
37
2
1
Order By: Relevance
“…(2007). Though overall emergence percentage was low in the present study, the selected genotypes had higher average emergence than results previously reported by Williams (2015).…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…(2007). Though overall emergence percentage was low in the present study, the selected genotypes had higher average emergence than results previously reported by Williams (2015).…”
Section: Resultscontrasting
confidence: 78%
“…It is one the few plant‐based foods which contain all the essential amino acids and certain antioxidants such as isoflavones (Velasquez & Bhathena, 2007; Wang & Murphy, 1994). In the past few years, some food companies, with the help of public universities, have begun production of edamame in the states of Arkansas, Washington, North Carolina, Kentucky, Illinois, Virginia, and Pennsylvania (Carson, Freeman, Zhou, Welbaum, & Reiter, 2011; Lumpkin, Konovsky, Larson, & McClary, 1993; Ogles, Guertal, & Weaver, 2016; Rao, Bhagsari, & Mohamed, 2002; University of Kentucky Extension, 2013; Williams, 2015; Wszelaki et al., 2005). The growing demand has attracted plant breeders and food industries to find suitable varieties for production in different regions of the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Horticultural research to facilitate domestic edamame production on a commercial scale is limited. The vegetable industry currently relies heavily on established grain-type soybean management guidelines, despite stark differences between the two types of cultivars and their end-use products (Williams, 2015;Zhang et al, 2013). Although some management techniques might translate from grain-type soybean to edamame, research to confirm or deny their appropriateness is lacking.…”
mentioning
confidence: 99%
“…Poor emergence is a common theme in field research on edamame (Duppong and Hatterman-Valenti 2005;Rao et al, 2002;Sanchez et al, 2005;Williams, 2015). Seedling emergence is affected by interactions among biotic, edaphic, and management factors (Arndt, 1965;Hamman et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation